A novel cancer therapy to stimulate oncogenic ERK signalling - Sugiura, Reiko (Henry Stewart Talks, 2018)
MAPK signalling and its relevance to cancer therapy, The discovery of ACA-28, The use of yeast within drug discovery, Effect of ACA-28 on the apoptosis of cancer cells, Implications of ACA-28 in cancer therapeutics